2010
DOI: 10.1074/mcp.m110.000661
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Proteomics and Metabolomics Profiling of Gastric Cardia Cancer Reveals Characteristic Dysregulations in Glucose Metabolism

Abstract: Gastric cardia cancer (GCC), which occurs at the gastricesophageal boundary, is one of the most malignant tumors. Despite its high mortality and morbidity, the molecular mechanism of initiation and progression of this disease is largely unknown. In this study, using proteomics and metabolomics approaches, we found that the level of several enzymes and their related metabolic intermediates involved in glucose metabolism were deregulated in GCC. Among these enzymes, two subunits controlling pyruvic acid efflux, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
90
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 57 publications
7
90
0
Order By: Relevance
“…In comparison with proliferating cells, quiescent cells exhibit a decrease in expression of glycolytic enzymes and an increase in expression of OXPHOS related enzymes [36][37][38]. In this study, we observed down-regulation of ALDOC, TPI1, and GAPDH, and upregulation of ATP5B in the excess GH1-treated pituitary ( Table 2).…”
Section: Cell Growth and Cell Proliferationsupporting
confidence: 42%
“…In comparison with proliferating cells, quiescent cells exhibit a decrease in expression of glycolytic enzymes and an increase in expression of OXPHOS related enzymes [36][37][38]. In this study, we observed down-regulation of ALDOC, TPI1, and GAPDH, and upregulation of ATP5B in the excess GH1-treated pituitary ( Table 2).…”
Section: Cell Growth and Cell Proliferationsupporting
confidence: 42%
“…The focus on the metabolic profile of the whole organism provides relevant information about specific cell types under different conditions, which is crucial for a more holistic understanding of cell properties and functions (Cai et al, 2010;Mintz-Oron et al, 2012). By using a combination of feature selection, pattern recognition, and multivariate data analysis approaches, metabolomic profiling aims to provide a comprehensive assessment of the alterations in the metabolite levels in cells (Lange et al, 2011;Stringari et al, 2011;Turnbaugh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Combining proteomics analysis with metabolic profiling is especially attractive, since metabolomics provides information in forming a functional interpretation of proteomics data, while proteomics analysis contributes to a better understanding of metabolomics data by highlighting participating enzymes and/or enzymatic pathways. The combination of proteomics and metabolomics has aided in elucidating the molecular mechanisms of various disorders, including cancer (Cai et al, 2010;Ma et al, 2012), psychiatric disorders Wesseling et al, 2013;Zhang et al, 2011), and cardiovascular disease (Mayr et al, 2008). Among these studies combining proteomics and metabolomics approaches, one research group has identified biomarker candidates and hippocampal metabolic changes with paroxetine treatment (Webhofer et al, 2012).…”
mentioning
confidence: 99%